2011
DOI: 10.1371/journal.pone.0027355
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Epigenetics of Human Breast Cancer: Synoptic Investigation of Targeted Genes, MicroRNAs and Proteins upon Demethylation Treatment

Abstract: BackgroundThe contribution of aberrant DNA methylation in silencing of tumor suppressor genes (TSGs) and microRNAs has been investigated. Since these epigenetic alterations are reversible, it became of interest to determine the effects of the 5-aza-2′-deoxycytidine (DAC) demethylation therapy in breast cancer at different molecular levels.Methods and FindingsHere we investigate a synoptic model to predict complete DAC treatment effects at the level of genes, microRNAs and proteins for several human breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…The decrease in SOX11 mRNA and protein levels in 5-AZA treated Granta519 and Rec1 MCL cell lines and the fact that the SOX11 promoter region is already hypomethylated in MCL (current data and1213) suggest that effect of 5-AZA on SOX11 levels might be indirect. Promoter methylation-independent effects of 5-AZA on certain genes were already reported in MCL15, AML16, colon cancer17 and in breast cancer18. Vegliante et al showed that the histone deacetylase (HDAC) inhibitor SAHA induced SOX11 expression in JVM2 and Raji cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…The decrease in SOX11 mRNA and protein levels in 5-AZA treated Granta519 and Rec1 MCL cell lines and the fact that the SOX11 promoter region is already hypomethylated in MCL (current data and1213) suggest that effect of 5-AZA on SOX11 levels might be indirect. Promoter methylation-independent effects of 5-AZA on certain genes were already reported in MCL15, AML16, colon cancer17 and in breast cancer18. Vegliante et al showed that the histone deacetylase (HDAC) inhibitor SAHA induced SOX11 expression in JVM2 and Raji cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…Real-time PCR reactions were performed in three replicates. The fold difference for each samples were calculated using the comparative Ct method (2 ÀDDCt ) [21,28].…”
Section: Quantitative Real Time Pcrmentioning
confidence: 99%
“…However, in cancer cells, they have been found hypermethylated, a phenomenon which leads to inappropriate gene silencing . Especially in BC cells, these silenced genes have been identified as proapoptotic genes ( HOXA5, TMS1 ), cell cycle‐inhibitor genes ( p16, RASSF1A ) or DNA repair genes ( BRCA1 ) …”
Section: Major Epigenetic Modifications In (Breast) Cancermentioning
confidence: 99%
“…30 Especially in BC cells, these silenced genes have been identified as proapoptotic genes (HOXA5, TMS1), cell cycle-inhibitor genes (p16, RASSF1A) or DNA repair genes (BRCA1). 3,31,32 CpG DNA methylation is carried out by DNA methyltransferases (DNMTs). Two types of DNMTs have been described: the "de novo" DNMTs (DNMT3A and DNMT3B) that establish the pattern of methylation during embryonic development, and the "maintenance" DNMTs (DNMT1) which are highly expressed during the S-phase of the cell cycle and are responsible for maintaining the pattern of methylation through adult development.…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation